PENGARUH KEPEMIMPINAN TERHADAP MOTIVASI KERJA DI PT. SWADAYA MUKTI PRAKARSA, KETAPANG - Fransiska Ekobelawati; Zulimi Zulimi; Marjono Marjono (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2023)
This research is based on phenomenon of a work motivation of higher education administration employee. It’s interesting to study the effect of leadership on the work motivation of higher education administration employee. This research uses quantitative method applying a survey approach. Respondents are education administration employees in PT. Swadaya Mukti Prakarsa, Desa Sempurna, Kecematan Sungai Laur, Kabupaten Ketapang, Kalimantan Barat with 55 respondents. This research result the hypothesis, can be said according to the hypotesis leadership had a significant effect on work motivation. It can been seen in α below 0,05 or below 5%. That indicate that hypotesis one accepted or relationship between leadership and work motivation is significant in this research. Leadership affectcs employee work motivation. That is, leadership to work motivation in higher education employee. Leadership is useful to motivate employee work in the organization especially in higher organization.